Analysis and control of the unloaded BI-directional DC/DC converter to perform an active damping function - Jusoh, Awang; Forsyth, A. J.; Salam, Zainal (Penerbit UTM Press, 2006)
The sub-system interaction and instability phenomena is a common problem in the Distributed Power System (DPS). The interaction arises because an individual converter known as constant power load (CPL), has internal control function such as to regulate the converter output voltage, which results in the converter tends to draw a constant power. The input impedance of CPL has a negative incremental input impedance, which tends to create instability as it is connected to a system. This paper presents the analysis and control of the DC-DC converter used to perform an active damping function in a DPS, comprising L-C filters and CPLs. The DC-DC converter was modelled using averaged technique. The small-signal analysis is performed and the controller was designed on such a way to regulate the converter input current. The design of the control loop parameters based on the frequency domain is demonstrated. The effectiveness of the active damping method was verified by MATLAB Simulink simulation.